Ultrasound-based measurement of optic nerve sheath to evaluate increased intracranial pressure on patients in emergency department - Jiang, Hai-dan; Shao, Hua-guo; Pan, Lin; Li, Hui (Frontiers in Neurology, 2025)
Background and aimsRecent studies reported that non-invasive imaging techniques for measuring optic nerve sheath diameter (ONSD) offer a novel diagnostic approach for intracranial pressure (ICP) elevation. However, whether ultrasound-measured ONSD sensitively evaluate the real-time ICP is unknown. This study explores the ability of different measurement modalities to predict ICP elevation, aiming to provide a superior non-invasive ICP monitoring technique for clinical practice.MethodsOptic nerve sheath (ONS) measurement using three modalities and ICP of 104 patients collected from January 2018 to May 2021 were analysis by correlation analysis and receiver operating characteristic curve analysis.ResultsSignificant correlations were observed between ICP and ONS measurement using three modalities (p < 0.001). According to the ROC analysis, if ONS long diameter > 5.55 mm, ONS vertical diameter > 5.75 mm, left ONS area > 25.05 mm2 or right ONS area > 25.73 mm2, the patient was considered to have elevated ICP.ConclusionUltrasonic transverse scanning, longitudinal scanning, and area-based measurement of the retrobulbar ONS are excellent screening tools for the diagnosis of ICP. These three methods exhibited nearly identical levels of correlation, sensitivity, and specificity. All three measurement approaches demonstrated capabilities in diagnosing elevated ICP.